Structural studies and cyclization of the neuroprotective octapeptide NAPVSIPQ to improve cell permeability. Issue 4 (11th July 2020) - Ernenwein, Dawn; St. John, Sarah E.; Stewart, Alistair J.; Morimoto, Bruce H.; Chmielewski, Jean; Lipton, Mark A.
Abstract: A secondary structural model for the neuroprotective octapeptide NAPVSIPQ in DMSO was developed using a combination of NMR spectroscopy and molecular dynamics simulations. On the basis of this model, four cyclized analogues of NAPVSIPQ were designed to improve its cell permeability with a long‐term view to oral delivery and increasing central nervous system (CNS) penetration. Testing of cell permeability through a monolayer of Caco‐2 cells demonstrated that three of the four cyclized analogues did exhibit up to 5‐fold improved permeability through the Caco‐2 monolayer. Additionally, none of the peptides appears to be P‐glycoprotein substrates subject to cellular efflux. Abstract :